2022
DOI: 10.3389/fvets.2022.1035175
|View full text |Cite
|
Sign up to set email alerts
|

Homing of radiolabelled xenogeneic equine peripheral blood-derived MSCs towards a joint lesion in a dog

Abstract: Osteoarthritis (OA) is a highly prevalent condition in dogs, causing a substantial reduction in quality of life and welfare of the animals. Current disease management focusses on pain relief but does not stop the progression of the disease. Therefore, mesenchymal stem cells (MSCs) could offer a promising disease modifying alternative. However, little is known about the behavior and the mode of action of MSCs following their administration. In the current case report, 99mTechnetium labelled xenogeneic equine pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, in that study, MSCs-IVt was performed immediately after the procedure, which is known to elicit inflammatory response within the first day [34]. Similarly, in a case study involving a dog with ACL rupture and synovitis, in vivo homing was observed 6 h after MSC-IVt [35]. Histological evidence also supports labeled MSCs within knee joint structures following IVt [13,16].…”
Section: Discussionmentioning
confidence: 90%
“…However, in that study, MSCs-IVt was performed immediately after the procedure, which is known to elicit inflammatory response within the first day [34]. Similarly, in a case study involving a dog with ACL rupture and synovitis, in vivo homing was observed 6 h after MSC-IVt [35]. Histological evidence also supports labeled MSCs within knee joint structures following IVt [13,16].…”
Section: Discussionmentioning
confidence: 90%
“…MSCs are multipotent stem cells that have the potential to differentiate into several types of progenitor cells (such as adipocytes, osteoblasts, and myoblasts), and are involved in the maintenance and regeneration of connective tissues 20 . They can be separated from numerous tissue types, such as bone marrow (BM) 21 , adipose tissue (AT) 22 , dental pulp 23 , peripheral blood 24 , hair follicle 25 , lungs 26 , the placenta 27 , the umbilical cord (UC) 28 , UC blood, Wharton’s jelly 29 , amnion 30 , and chorion 31 . Among these, MSCs derived from BM, AT, and UC are the three most utilized in preclinical and clinical research 32 .…”
Section: Introductionmentioning
confidence: 99%